Non-Catalytic And Solvent-Free Esterification Of Acetic Acid With Ethanol Using Coiled Flow Inverter For Ethyl Ethanoate Synthesis In Food Industry - Mohamad Alias, Nurul Aina (Universiti Sains Malaysia, 2021)
Non-catalyzed and solvent-free esterification of ethanol and acetic acid has been conducted in a novel intensified equipment, coiled flow inverter (CFI) to study the mixing performance of CFI in obtaining higher amount of ethyl ethanoate in a shorter time. The experimental study was carried out for very low laminar Reynold Number (Re) varies from 0.26 to 0.51 and for high laminar Re starting from 25 to 75 at constant volume ratio 3 : 1 of ethanol to acetic acid and at constant temperature 80℃. The effects of applying different Re towards the acid conversion and ethyl ethanoate concentration were examined. The mixing profile of fluids in laminar flow conditions were validated in COMSOL Multiphysics 5.5 while the aftermath of changing two CFI parameters either internal diameter of tube or coil diameter,was investigated via computational fluid dynamics (CFD) analysis in COMSOL. The experimental results showed that at very low laminar Re condition, high conversion ( > 80%) of ethyl ethanoate can be obtained as the Re decreased approaching 0. However, moderate conversion ( > 75%) was attained at shorter time when Re increased in high laminar Re condition due to efficient convective mixing created in CFI at high flow rates. It was also observed that smaller diameter of coil able to create more flow inversions while smaller inner diameter of tube promotes greater mixing flow efficiency in the tube. Optimum diameter of coil and tube inner diameter are crucial to be known as it can promote higher mixing efficiency and product concentration for processing ethyl ethanoate at shorter time for food industry.